Community-acquired bacteremia among HIV-infected and HIV-exposed uninfected children hospitalized with fever in Mozambique. (August 2021) - Kenga, Darlenne B.; Gebretsadik, Tebeb; Simbine, Samuel; Maússe, Fabião E.; Charles, Pedro; Zaqueu, Ernesto; Fernando, Hermenegilda F.; Manjate, Alice; Sacarlal, Jahit; Moon, Troy D.
Highlights: 12% of HIV-infected or -exposed uninfected kids had bacteremia at hospitalization For children found to have bacteremia, in-hospital mortality was 19% Nearly 70% of Staphylococcus aureus isolates were methicillin resistant (MRSA) ~50% of Klebsiella isolates had extended-spectrum beta-lactamase (ESBL) production High MRSA and ESBL has implications for the empiric antibiotics used in Mozambique ABSTRACT: Background: Bacteremia is a major cause of morbidity and mortality worldwide. Children infected with HIV present with patterns of bacteremia generally associated with poor prognosis. In Mozambique, data on bacteremia are sparce. Methods: We conducted an observational study of HIV-infected and HIV-exposed uninfected children, aged 0-59 months, hospitalized with fever between April 1, 2016 and February 28, 2019. A single bacterial culture was collected at admission. Descriptive statistics were used to summarize microorganisms detected and antibiotic susceptibility testing. Results: A total of 808 HIV-infected (90%) and HIV-exposed uninfected (10%) children were enrolled. Blood culture positivity was 12% (95% CI: 9.9%-14.4%). Five organisms accounted for most cases: Staphylococcus Aureus (37%), Klebsiella spp (11%), Salmonella spp (11%), Escherichia Coli (9%) and Micrococcus (7%). Antibiotic resistance was common. Nearly 70% of Staphylococcus Aureus were methicillin-resistant and roughly 50% of Klebsiella had ESBL production. Conclusion: Community-acquired bacteremia was common in HIV-infected and HIV-exposed uninfected children hospitalized in Mozambique with a febrile illness. High rates of MRSA and ESBL producing organisms has implications for empiric antibiotics utilized in Mozambique. Longitudinal data on the prevalence and antimicrobial resistance patterns of important pathogens are badly needed to guide policy for drug formulary expansion and antibiotic prescription guidelines.